From feminism to gender equality - Huynh, Samantha (2017)
There is a dominating image of Sweden as a gender-equal and environmentally friendly nation with progressive policies. Since the Swedish Government has claimed to be feminist and that all policies therefore must be feminist, including energy policy, in this thesis I have explored what interpretations exist in regards to feminist energy policy because feminism and energy are two areas that are rarely connected. The material for this study has been limited to three policy documents and interviews with eight people who work with energy issues in different ways. For my analysis I have used a Critical Discourse Analysis approach that is predominantly influenced by Carol Bacchi and Norman Fairclough and in combination with Feminist theory by Paulina de los Reyes, Sara Ahmed and bell hooks I have drawn the conclusion that feminism and feminist energy policy have been reduced to gender equality and the quantitative representation of women within the valued male-dominated energy sector. Furthermore, feminist energy policy can be used as a tool to produce a sense of nation-pride and to confirm the progressiveness of the Swedish welfare state. In a larger context, the interpretations of feminism and feminist energy policy that I have identified operate within the dominating discourse of neoliberalism and its agendas of marketization and labour exploitation, which favour technological innovation as a means for international competitiveness and economic (and “green”) growth. Thus, women are represented as being the problem, as choosing wrong and as needing a push to choose “right” for both Sweden’s (economic) development and the greater good of our natural environment. The identified simplistic views of feminist energy policy and gender equality accept the premise, although not explicitly, that the group “women” is a large homogenous group of white and middle-class women. This not only obscures the struggles of those who fall outside of this description but also reproduces the notion that inequality only exists between women and men. This study suggests that there is a lack of intersectional perspectives to understand the complexity of inequality and marginalisation in regards to energy policy in Sweden and that future research could take this into consideration.